Sejarah Perkembangan Sistem Pendidikan Di Filipina - Syarifah Rahmayani; Mislaini Mislaini; Oktaviana Imroatun Cahyati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The history of the development of the education system in the Philippines, which reflects the nation's long journey through various cultural influences and colonialism. Starting from the informal education that existed in pre-colonial societies, this article outlines the significant changes that occurred with the arrival of Spanish colonialists in the 16th century, who introduced a formal education system with a focus on Catholic teachings. Furthermore, the transition to a modern education system occurred under American colonial rule in the early 20th century, where English was introduced as the language of instruction and democratic values were promoted. This article also explores the challenges facing the Philippine education system post-independence, including efforts to create inclusive and relevant education. With an in-depth analysis of these various phases of development, this article aims to provide a better understanding of the dynamics of education in the Philippines and its impact on society today.